2013
DOI: 10.1016/j.canlet.2013.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic combination therapy with nanoliposomal C6-ceramide and vinblastine is associated with autophagy dysfunction in hepatocarcinoma and colorectal cancer models

Abstract: Autophagy, a catabolic survival pathway, is gaining attention as a potential target in cancer. In human liver and colon cancer cells, treatment with an autophagy inducer, nanoliposomal C6-ceramide, in combination with the autophagy maturation inhibitor, vinblastine, synergistically enhanced apoptotic cell death. Combination treatment resulted in a marked increase in autophagic vacuole accumulation and decreased autophagy maturation, without diminution of the autophagy flux protein P62. In a colon cancer xenogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 49 publications
0
54
0
Order By: Relevance
“…Cer is the simplest molecule in this family, and it serves as a precursor for the synthesis of the three main types of complex SLs (SMs, GSLs, and gangliosides), respectively. Bioactive SLs, together with Cer, sphingosine (SPH), and sphingosine-1-phosphate (S1P), are secondary messenger molecules that regulate a diverse array of intra-and intercellular processes (3,56,60). They are important structural blocks because of their bioactive secondary messenger molecules in which they function in a different pattern of cellular processes.…”
Section: Sphingolipid Steady State In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Cer is the simplest molecule in this family, and it serves as a precursor for the synthesis of the three main types of complex SLs (SMs, GSLs, and gangliosides), respectively. Bioactive SLs, together with Cer, sphingosine (SPH), and sphingosine-1-phosphate (S1P), are secondary messenger molecules that regulate a diverse array of intra-and intercellular processes (3,56,60). They are important structural blocks because of their bioactive secondary messenger molecules in which they function in a different pattern of cellular processes.…”
Section: Sphingolipid Steady State In Health and Diseasementioning
confidence: 99%
“…Oral administration of anti-LPS antibodies along with GSLenriched adjuvant compounds was effective in ameliorating NASH and diabetes in both animal models and humans (2,3,120,124,193,194). These effects were associated with alterations of Tregs and NKT cells, thereby supporting a potential effect of GSLs on the gut-microbiome-immune system axis.…”
Section: Effects Of Fxr Agonists and Anti-lps In Nash Are Partially Amentioning
confidence: 99%
“…Microtubules are required for autophagosomal biogenesis and degradation, and vinca alkaloids disrupt autophagosome maturation/degradation by preventing the movement of autophagosomes and their fusion with lysosomes (18). Several studies have demonstrated that the treatment of cancers with agents that induce autophagy in combination with agents that block autophagosome maturation/degradation results in synergistic apoptotic cell death (19)(20)(21). Myeloma cells require a basal level of autophagy for survival and the pharmacologic or genetic inhibition of autophagy caused myeloma cells to die (22).…”
Section: Effect Of Vincristine or Doxorubicin On Autophagy Induced Bymentioning
confidence: 99%
“…Anticancer activity was assayed against MCF-7 (human breast cancer cell line) (11). An in vitro and in vivo study suggests a synergistic anticancer activity of a nanoliposomal C6-ceramide and vinblastine combination, potentially lead by an autophagy mechanism (12).…”
Section: Diterpenoidmentioning
confidence: 99%